Synthesis of C3-alkylated benzofurans via palladium-catalyzed regiocontrolled hydro-furanization of unactivated alkenes. Issue 1 (20th November 2020) - Zhu, Chi-Fan; Gao, Cong-Hui; Hao, Wen-Juan; Zhu, Yi-Long; Tu, Shu-Jiang; Wang, De-Cai; Jiang, Bo
Abstract : A new chelation-controlled hydrofuranization of unactivated olefins with α-alkynyl arylols is reported for the first time, and used to produce a wide range of C3 -alkylated benzofurans with generally good yields under mild conditions. Abstract : A new chelation-controlled hydrofuranization of unactivated olefins with α-alkynyl arylols is reported for the first time, and used to produce a wide range of C3 -alkylated benzofurans with generally good yields under mild conditions. A bidentate directing group is used to suppress β-hydride elimination and in turn facilitate a protodepalladation event. In addition to 100% atom utilization, good functional group tolerance and mild conditions, the present catalysis did not demand any additional ligand, additives and bases/acids, making the transformation simple and facile and it thus opens new avenues for catalytic difunctionalization of alkynes and olefins.